Population dynamics of narrow-barred Spanish mackerel (Scomberomorus commerson) in the Persian Gulf, Bushehr province, Iran - Motlagh, Seyyed Aminollah Taghavi; Shojaei, Mehdi Ghodrati (Indian Journal of Fisheries, 2011)
The kingfish, Scomberomorus commerson fishery in the Iranian waters of Persian Gulf and Oman Sea has increased from 3,939 t in 1997 to 8,149 in 2003, recording a two fold increase over the period. Bulk of the catch is landed by gillnets followed by handlines. Monthly samples of S. commerson for length-weight measurements were collected from the Bushehr province for the period from May 2000 to May 2001. The data were used to estimate length-weight relationship as well as growth parameters, using the modal progression method. The von Bertalanffy growth parameters, L, K, and t0 were estimated as 189 cm, 0.24 year-1 and -0.29 year-1, respectively. Using the length-converted catch curve, total mortality (Z) was estimated as 1.65 per year. Subtracting the natural mortality value from this estimate (F= Z-M) resulted in a fishing mortality (F) of 1.3, which gives an exploitation rate (E) of 0.78. The results confirm that exploitation of kingfish in the Persian Gulf and Oman Sea appears to be heavy, which is consistent with similar studies in Omani and Saudi waters. Considering the decline of kingfish catches in Omani waters, the possible implementation of management measures in Iranian waters should be formulated.